Karakteristik Populasi Katak Sawah (Fejervarya cancrivora) Di Persawahan Sungai Raya Kalimantan Barat - Ari Hepi Yanti, Deki saputra, Tri Rima Setyawati (Universitas Tanjungpura, 2014)
Paddy frogs ( F. cancrivora ) is one the member of the Class Amphibia Order Anura which is important ecologically and economically. This study aims to investigate the characteristics of paddy frog populations (F. cancrivora) which include density, sex ratio, fecundity and gonad maturity level (GML) . The study was conducted from August to September 2013 in the paddy field of Sugai Raya, Kubu Raya Regency in West Kalimantan province. The sampling method was plot method with the size of 20x20 m in wich the samples was directly captured with bare hand. The density of F. cancrivora in paddy fields of Sungai Raya in Kubu Raya regency is 1.01 individuals/m2. The sex ratio of male and female F. cancrivora is 1 : 1.8. Female F. cancrivora can produce 4,808-18,260 eggs in one spawning. F. cancrivora with the body of 5.5 cm in length has entered phase IV of gonad maturity level. The temperature around the site ranged from 240 to 260C and humidity was 65 %. These are good conditions for the development and reproduction of F. cancrivora.